CORONARY PERFORATION DURING PERCUTANEOUS CORONARY INTERVENTION; EXPERIENCE AT ARMED FORCES INSTITUTE OF CARDIOLOGY - Siddiqui, Abdul Hameed; Tayyub, Farhan; Islam, Zafar ul; Aziz, Sohail; Samore, Naseer Ahmed (Pakistan Armed Forces Medical Journal, 2020)
Objective: The study was conducted to find out the frequency of coronary perforation during percutaneous coronary intervention. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at AFIC/NIHD Rawalpindi from Jan 2010 to Mar 2012. Materials and Methods: We report the incidence, management, and clinical outcome of coronary perforation in 12 of 9868 patients (0.12%) undergoing percutaneous coronary interventions between Jan 2010 and Mar 2012. Results: The most commonly involved artery was left anterior descending artery (66.7%) followed by circumflex (16.7%) and right coronary artery (16.7%). There was one type I perforation (8.3%), eight type II perforations (66.6%) and three type three perforations (25%). One fourth of the coronary perforations were guide wire related. Conventional strategies to treat perforations i.e., prolonged balloon inflations, reversal of anti-coagulations in selected cases and covered stents were used. There was one death, one emergency surgery and one Q wave myocardial myocardial infarction. Pericardial effusion occurred in 3 out of 12 patients with cardiac tamponade occurring in 2 patients requiring emergency peri cardiocentesis.